Integration of Pastoral Counseling in Theological Education: Qualitative Research in Building Counselor Competence - Jayadi, Lionarto Erson; Phang, Steven; Wahyuningsih, Tri (Indonesian Journal of Religious, 2024)
This article discusses the importance of integrating pastoral counseling into theological education to build a more holistic and effective church counselor competence. Although some theological education institutions have included pastoral counseling in their curriculum, many still focus on teaching theory without addressing the practical skills needed for church ministry. This study reveals that combining psychological and theological principles in theological education can help prepare church leaders who are better equipped to handle the emotional and spiritual challenges of the congregation. The research method used is qualitative, based on in-depth interviews and documentation. With a more comprehensive and practice-based approach, theological education can equip future church counselors with the skills necessary to provide more effective and relevant support. Therefore, this study recommends that churches and theological educational institutions collaborate in designing a more innovative curriculum to enhance the quality of pastoral counseling services.   Artikel ini membahas pentingnya integrasi konseling pastoral dalam pendidikan teologi untuk membangun kompetensi konselor gereja yang lebih holistik dan efektif. Meskipun beberapa institusi pendidikan teologi telah memasukkan konseling pastoral dalam kurikulumnya, banyak yang masih memfokuskan pengajaran pada teori tanpa memperhatikan keterampilan praktis yang diperlukan untuk pelayanan gereja. Penelitian ini mengungkapkan bahwa penggabungan prinsip psikologis dan teologis dalam pendidikan teologi dapat membantu mempersiapkan pemimpin gereja yang lebih siap menangani tantangan emosional dan spiritual jemaat. Metode penelitian ini menggunakan kualitatif berbasis wawancara yang mendalam dan dokumentasi. Dengan pendekatan yang lebih komprehensif dan berbasis praktik, pendidikan teologi dapat membekali calon konselor gereja dengan keterampilan yang dibutuhkan untuk memberikan dukungan yang lebih efektif dan relevan. Oleh karena itu, penelitian ini memberikan rekomendasi agar gereja dan lembaga pendidikan teologi bekerja sama dalam merancang kurikulum yang lebih inovatif untuk meningkatkan kualitas pelayanan konseling pastoral.